Produção de cerveja Pilsen com adição de diferentes matérias-primas amargas da região Sul do Brasil - CAVALCANTE, GUILHERME PIMPÃO (2016)
Throughout history various herbs were used in the preparation of beer, with the main intention to preserve the product. Hops stood out among them, because it has natural preservatives and sensory properties. Breweries are betting on the production of beer with the addition of special ingredients, in addition to hops. So the search for a differentiated product able to satisfy the palate of the most discerning of consumers becomes critical. This work had as main goal the use of different bitter plants in the production of beer Pilsen, in order to improve sensory characteristics by creating new beer styles, decreasing the costs related to raw materials. The raw materials introduced into the brewing process were boldo-of-chile (Peumus boldus), green coffee (Coffea arabica), yerba mate (Ilex paraguariensis) and wormwood (Artemisia absinthium), all easily found in southern Brazil. These plants in addition contribute to the bitterness of the drink, also have high antioxidant activity and phenolic content that, when ingested, have numerous benefits to the body. The dosage of each herb in the manufacture of beverages was established by performing experimental designs of type of simplex centroid mixtures. Based on these designs, four different beers were produced. The elaborated drinks were subjected to sensory analysis of hedonic scale. It was found that the beer produced from a mixture of hops, wormwood and green coffee obtained the highest rates of purchase intent, acceptance and preference. In addition, were evaluated the physicochemical parameters of beers such pH and bitterness index. The physico-chemical parameters and sensory analysis indicated the possibility of production of beers with addition of some herbs. Reducing the concentration of hops due to the use of regional bitter herbs made the process less expensive while maintaining the quality of the final product.